Characterization of Goblet Cells in a Pterygium Biopsy Using Laser Scanning Confocal Microscopy and Immunohistochemistry. Issue 8 (August 2016) - Colorado, Luisa H.; Pritchard, Nicola; Cronin, Brendan G.; Efron, Nathan
Abstract : Purpose: To confirm that structures presumed to be GCs observed using laser scanning confocal microscopy (LSCM) are actually GCs. Methods: A single tissue sample was obtained from a pterygium that was freshly excised from a 33-year-old male. After viewing what were believed to be GCs in the tissue sample using LSCM, the same sample was observed using laboratory confocal microscopy and immunohistochemistry. GCs were identified by a combination of classic morphologic appearance and the use of immunofluorescence to antibodies for mucin 5AC and cytokeratin-7. The LSCM and immunohistochemistry results were compared. Results: Using LSCM, GCs were observed between 7 and 41 μm deep, at the level of the superficial basal cells of the tissue sample. GCs were estimated to have a diameter of 35–40 μm near the surface and 20–30 μm in the deeper layers. A small dark dot was visible in some GCs, indicating cell nuclei and/or the opened apical portion of cells representing the site of mucin release. GCs were more reflective and larger than the surrounding cells. Positively stained GCs in immunofluorescence showed a similar distribution pattern to those observed with LSCM. The tissue sample stained intensely for GC–specific mucin type 5AC. Conclusions: The pattern of discrete, large reflective cells observed using LSCM are likely to be GCs.